Case Grammar in the Movie Ã¢â‚¬Å“The GentlemenÃ¢â‚¬Â Based on the Perspective of Charles J. Fillmore - Basid, Abdul; Maghfiroh, Devi Laila (Universitas Negeri Semarang, 2021)
This research aims to identify the proposition in the movie